2020
DOI: 10.1039/d0ra04186f
|View full text |Cite
|
Sign up to set email alerts
|

Digital light processing 3D printing of modified liquid isoprene rubber using thiol-click chemistry

Abstract: Elastomer-based 3D objects with good resolution are fabricated by additive manufacturing of photo-reactive liquid rubber formulations with digital light processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…165,166 For example, Strohmeier et al reported the use of divinyl ethers as reactive diluents to reduce the viscosity of methacrylated liquid isoprene rubber from 79 Pa s to <6 Pa s, allowing it to be used with DLP printing. 167 Photosensitive slurries used in ceramic VP need to carefully manage their solid loadings such that they are low enough for their viscosities to be manageable but still sufficiently high that the final ceramic part has the desired properties. 114 Liu et al demonstrated this in their fabrication of alumina with DLP printing: materials made from slurries with 55 vol% of particles exhibited the least shrinkage, but the high viscosities affected the recoating process and resulted in internal defects that weakened the material.…”
Section: Viscositymentioning
confidence: 99%
“…165,166 For example, Strohmeier et al reported the use of divinyl ethers as reactive diluents to reduce the viscosity of methacrylated liquid isoprene rubber from 79 Pa s to <6 Pa s, allowing it to be used with DLP printing. 167 Photosensitive slurries used in ceramic VP need to carefully manage their solid loadings such that they are low enough for their viscosities to be manageable but still sufficiently high that the final ceramic part has the desired properties. 114 Liu et al demonstrated this in their fabrication of alumina with DLP printing: materials made from slurries with 55 vol% of particles exhibited the least shrinkage, but the high viscosities affected the recoating process and resulted in internal defects that weakened the material.…”
Section: Viscositymentioning
confidence: 99%
“…In addition, the conversion of the metal precursor by sol-gel can be determined via Equation (2), where w 1 refers again to the residual weight of the sample and w 3 to the mass of reinforcing filler, which should have been generated assuming quantitative conversion. [23,49,51,59] Precursor conversion %…”
Section: Sol-gel Derived In Situ Fillersmentioning
confidence: 99%
“…[1] Besides traditional manufacturing, new technologies such as additive manufacturing are on the rise, which enable the preparation of tailor-made rubber products. [2,3] Tough, the most innovative technology would be negligible without the reinforcing power of fillers.…”
Section: Introductionmentioning
confidence: 99%
“…[41] This way, biological and chemical modifications can be conducted in the latex phase not only for NR but for other diene rubbers as well. [53] Modifications on latex phase include preparation of nanoparticles, [54,55] composites, [56][57][58] degradation studies, [5,44] vulcanization, and introduction of cross-links, [59,60] functionalization with organic compounds [14,61,62] and among others. [46,63]…”
Section: Modifications Of the Latex Phasementioning
confidence: 99%
“…Schlögl and coworkers employed thiol-ene reactions to photocross-link liquid isoprene rubber to obtain precise structures by 3D printing. [59] Zhong et al reported the preparation of ultrathin honeycomb-patterned membranes. [138] The authors cross- linked the commercially available polystyrene-b-polyisoprene-bpolystyrene triblock copolymer and an amphiphilic copolymer based on polystyrene using a tri-thiol to build the cross-links.…”
Section: Rubber Modifications Via Thiol-x Reactionsmentioning
confidence: 99%